2014
DOI: 10.1038/sc.2013.164
|View full text |Cite
|
Sign up to set email alerts
|

Pain and fatigue as mediators of the relationship between mobility aid usage and depressive symptomatology in ambulatory individuals with SCI

Abstract: Study design Cross-sectional cohort study. Objectives To investigate a mediational model where pain (intensity and interference) and fatigue mediate the relationship between the use of mobility aids and moderate-to-severe depressive symptomatology among ambulatory participants with spinal cord injury (SCI). Setting A medical university in the southeastern United States. Methods Ambulatory adults (N = 652) with chronic SCI responded to a mail-in survey. The Patient Health Questionnaire-9 was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The association of depressive symptoms with functional limitation was examined; however, it is possible that those with functional limitations may result in higher levels of depressive symptoms. DiPiro and colleagues 21 found that pain and fatigue may mediate the relationship between mobility and depressive symptoms. The study did not examine how individuals in the comorbid group may differ from those with only pain or depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The association of depressive symptoms with functional limitation was examined; however, it is possible that those with functional limitations may result in higher levels of depressive symptoms. DiPiro and colleagues 21 found that pain and fatigue may mediate the relationship between mobility and depressive symptoms. The study did not examine how individuals in the comorbid group may differ from those with only pain or depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether depression has a unidirectional effect on fatigue (that is, depression causes fatigue) or whether the relationship is more complex. For example, a recent study on the relationship between mobility device usage and depressive symptomology in SCI found pain and fatigue to mediate the relationship, 26 supporting the concept of a more complex relationship between these factors. Regardless of direction of the effect, the associations of both depression and fatigue with participation are notable and speak to the need for research focused on treatment for depression and fatigue and the resultant effect on participation.…”
Section: Discussionmentioning
confidence: 97%
“…Authors observed that fatigue was negatively correlated with social integration and psychological functioning. DiPiro et al 33 observed disabling fatigue in 10.3%…”
Section: Discussionmentioning
confidence: 99%